Assessing financial metrics and Sharia Healthcare stock return amid Indonesia’s market volatility - Firman Setiawan; Catur Guritmo; Arif Zunaidi (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2024)
The present research aims to analyze how financial metrics reflecting profitability, liquidity, and solvency affect the profit performance of sharia-compliant equities in the healthcare industry amid the COVID-19 pandemic. This investigation employs a panel data regression methodology, utilizing a sample of medical services businesses that are publicly traded on the Indonesia Stock Exchange throughout this time frame from 2020 to 2022. The estimation model applied is the Fixed Effect Model (FEM) using Eviews 13 software. Hypothesis testing is conducted using t-tests and F-tests to ensure the robustness of the results. The findings reveal that simultaneously, ROA, ROE, EPS, NPM, CR, and DER have a significant effect on the return of sharia healthcare stocks. Partially, the results of this study show that EPS, CR, and DER have a significant effect on the return of sharia healthcare stocks. ROA, ROE, and NPM metrics had no substantial statistical implications. Theoretically, this study enriches the Islamic financial literature by showing that some financial ratios can affect Islamic stocks differently than conventional stocks during crises. In practical terms, these findings provide valuable insights for financial professionals to refine investment strategies, particularly in the healthcare sector during market volatility.